IMPLEMENTATION OF A COMPREHENSIVE BURN MANAGEMENT SYSTEM IN INDUSTRIAL ACTIVITIES (MANAGEMENT AND PREVENTION) - Sukmawati Tansil Tan; Yohanes Firmansyah; Edwin Destra; Yana Sylvana; Hanna Wijaya; Michelle Angelika S (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Background: Burns are a form of trauma that occurs as a result of human activities in the household, industry, traffic accidents, and natural disasters. The most vulnerable burn sufferers are women because their main role in the family is that many are in contact with fire and electricity such as cooking and ironing. Improper handling of burns can have an impact that will harm the patient.The purpose of this activity is to increase knowledge about burn injuries, as well as appropriate emergency first aid for burns to PT. KP employees.Methods: this program is given with the lecture method, and the presentation of the material uses a laptop audio-visual tool and online media in the form of zoom. After the presentation of the material, it was continued with the screening of a first aid education video for burn injuries, after the video playback was continued with a simulation/demonstration of the procedures for first aid for burn injuries including introducing the types of materials and drugs recommended for first aid burns. The session ends with a question and answer session and evaluationResults: Participants understood the general description of burns and their dangers and participants were able to understand proper first aid treatment. Participants can answer questions from the presenters and discuss the material presented.Conclusion: there is an increase in knowledge and understanding of the dangers of burns and first aid treatment for burns.